Homonyms in medicine; a perspective - Khalid Al Aboud (Our Dermatology Online, 2015)
In linguistics, a homonym is, in the strict sense, one of a group of words that share spelling and pronunciation but may have different meanings. Thus homonyms are simultaneously homographs (words that share the same spelling, regardless of their pronunciation) and homophones (words that share the same pronunciation, regardless of their spelling) [1].